2014
DOI: 10.4049/jimmunol.1400133
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor Promotes Clearance of Pneumococcal Colonization

Abstract: Human genetic polymorphisms associated with decreased expression of macrophage migration inhibitory factor (MIF) have been linked to the risk of community-acquired pneumonia (CAP). Since Streptococcus pneumoniae is the leading cause of CAP and nasal carriage a precursor to invasive disease, we explored the role of MIF in the clearance of pneumococcal colonization in a mouse model. MIF-deficient mice (Mif-/-) showed prolonged colonization with both avirulent (23F) and virulent (6A) pneumococcal serotypes compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 57 publications
7
33
0
Order By: Relevance
“…The observation that MIF is a genetic marker of morbidity and mortality of pneumococcal meningitis is in line with the results obtained in animal models of sepsis and in clinical studies that have linked high levels of MIF with life-threatening bacterial infections (21,22,(46)(47)(48)(49). In a murine model of pneumococcal colonization, the clearance of pneumococci from the nasopharynx, a critical step in the pathogenesis of invasive pneumococcal diseases, was more rapid in wild-type mice than in MIF-deficient mice (45). This finding suggested that MIF might be a protective factor against pneumococcal diseases.…”
Section: Discussionsupporting
confidence: 68%
“…The observation that MIF is a genetic marker of morbidity and mortality of pneumococcal meningitis is in line with the results obtained in animal models of sepsis and in clinical studies that have linked high levels of MIF with life-threatening bacterial infections (21,22,(46)(47)(48)(49). In a murine model of pneumococcal colonization, the clearance of pneumococci from the nasopharynx, a critical step in the pathogenesis of invasive pneumococcal diseases, was more rapid in wild-type mice than in MIF-deficient mice (45). This finding suggested that MIF might be a protective factor against pneumococcal diseases.…”
Section: Discussionsupporting
confidence: 68%
“…Colonization studies in mice have shown that the increased inflammation induced by its sole toxin, pneumolysin, accelerates the eventual clearance of the organism from its niche on the mucosal surface of the URT (Das et al, 2014; Matthias et al, 2008; van Rossum et al, 2005). This raises the question of why an organism dependent on a commensal lifestyle expresses a toxin that is both damaging to its obligate host and promotes its clearance (Weiser, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of MARCO (macrophage receptor with collagenous structure), though not directly responsible for pneumococcal uptake by upper respiratory tract macrophages, contributes to monocyte and macrophage recruitment, Ccl2 upregulation, and clearance of pneumococcal carriage (27). Macrophage migration inhibitory factor is also required during pneumococcal colonization to sustain the presence of macrophages, Ccl2 upregulation, and clearance (22). Expression of the microRNA miR-155 also contributes to Th17 induction and macrophage recruitment during pneumococcal carriage (117).…”
Section: Immune Evasion and Persistencementioning
confidence: 99%
“…Paradoxically, macrophage recruitment, and eventual clearance, requires pneumococcal expression of its toxin, pneumolysin (22). It may seem counterintuitive for a colonizing organism to induce the specific host response that clears it, but it is possible that persistence in the respiratory tract is sacrificed at the expense of inducing a more robust inflammatory response, which could promote nutrient acquisition and transmission to a new host (129).…”
Section: Immune Evasion and Persistencementioning
confidence: 99%